Peran kewirausahaan dalam mendorong inovasi dan pertumbuhan ekonomi pada era globalisasi - Feti Fatonah; Yerico Siahaan; Hanif Firjatullah; Hendra Pangaribuan; Mario Steven (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2026)
Entrepreneurship has become a key factor in driving economic development in the dynamic era of globalization. This study uses literature review and empirical data analysis methods to evaluate the role of entrepreneurship in innovation and economic growth. The results show that entrepreneurship can create jobs, introduce product and business process innovations, and enhance business competitiveness at both local and global levels. In addition, it was found that the integration of digital technology in entrepreneurial activities plays a significant role in accelerating the innovation process and expanding market access. Factors such as entrepreneurial education, government policy support, and a conducive business ecosystem also strengthen the positive impact of entrepreneurship on economic growth. In conclusion, the development of technology-supported entrepreneurship, cross-sector collaboration, and appropriate policies are crucial to achieving inclusive, sustainable, and adaptive economic growth in response to global changes